Performance Analysis of Blockchain Consensus Algorithm in Unmanned Aerial Vehicle Ad Hoc Networks - Xuan Huang; Dongyan Huang (Drones)
Blockchain technology is a competitive solution to address the prevailing data security concerns in unmanned aerial vehicle (UAV) networks. However, wireless communication links between UAV nodes are vulnerable to electromagnetic interference and competition due to limited spectrum resources. Consequently, a comprehensive analysis of blockchain performance within UAV network environments is imperative for the effective deployment and optimization of blockchain technology. This paper presents two theoretical models. The first model assesses the impact of the Carrier Sense Multiple Access with Collision Avoid (CSMA/CA) channel access protocol on the latency and throughput of the chained HotStuff consensus algorithm. The second model considers the movement characteristics of UAV nodes in three-dimensional space and the complexity of the communication environment. The aim of the second model is to calculate the consensus failure probability of UAV networks under electromagnetic interference. The results demonstrate that the theoretical values closely match the actual simulation outcomes.